Valvular heart disease - Wang, Andrew (Contemporary cardiology, 2009)
Challenges for the treatment of valvular heart disease include the growing need for effective yet less invasive interventions and therapies to treat these progressive conditions. With the development of potential new treatments, it is crucial for cardiac physicians to be well informed on the pathophysiology, assessment, treatment options and their outcomes of valvular diseases. Written by a highly experienced and internationally recognized group of cardiologists, cardiac surgeons, and researchers, Valvular Heart Disease offers insights into the widely varying hemodynamic effects and clinical course of heart valve conditions, as well as the contemporary management of these conditions. Offering a broad perspective on these diseases, Valvular Heart Disease expands on the recent guidelines developed by the major heart societies in the United State and Europe. Morphologic aspects of valvular heart disease - Cellular pathogenesis of degenerative valvular heart disease: from calcific aortic stenosis to myxomatous mitral valve disease - Ventricular adaptation to valvular heart disease - Physical examination in valvular heart disease - Clinical hemodynamics in valvular heart disease - Echocardiographic assessment of native valve function - Aortic stenosis - Aortic regurgitation - Mitral stenosis - Mitral regurgitation - Tricuspid stenosis and regurgitation - Pulmonary valve stenosis and regurgitation - Contemporary considerations in aortic valve surgery - Contemporary considerations in mitral valve surgery - Surgery of the tricuspid and pulmonary valves - Medical therapy of valvular heart disease - Percutaneous valve replacement - Percutaneous balloon valvuloplasty and mitral valve repair - Post-operative care of the patient undergoing valve surgery - Prosthetic valve dysfunction - Infective endocarditis - Exercise and noncardiac surgery in valvular heart disease - Valvular heart disease and pregnancy.